Electrochemically mediated ATRP process intensified by ionic liquid: A “flash” polymerization of methyl acrylate - Guo, Jun-Kang; Zhou, Yin-Ning; Luo, Zheng-Hong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2019)
[Display omitted] •An extremely fast and well controlled polymerization was achieved by using IL as solvent.•Both the supporting electrolyte and organic solvents could be replaced by IL.•The acceleration effect on polymerization rate was interpreted via experiment and modeling.•This work enriched the knowledge of reaction features of eATRP. An electrochemically mediated atom transfer radical polymerization (eATRP) of methyl acrylate (MA) in 1-butyl-3-methylimidazolium hexafluorophosphate (BMIM-PF6) ionic liquid (IL) was reported. Remarkably, the kinetic results revealed an extremely fast and well controlled polymerization in the presence of tris(2-(dimethylamino)ethyl)amine (Me6TREN). The monomer conversion reached more than 90% within a period of 300 s. Computational and simulation results indicated that the IL induced acceleration of polymerization can be attributed to the increased value of kt/kp2 compared to the associated literature value. Additionally, polymerizations under different conditions, including ligand types, monomer/IL ratios, catalyst loadings, and targeted degrees of polymerization were explored. All the kinetic plots suggested superfast polymerization rates with good control over molecular weight and dispersity. Furthermore, the livingness of MA polymerization was confirmed by chain extension experiment. This work provides a new insight into eATRP in IL through experimentation and simulation and thus enriches the knowledge of reaction features of eATRP.